2014
DOI: 10.1159/000362158
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Occurrence of Early Gastric Carcinoma and Mucosa-Associated Lymphoid Tissue Lymphoma of the Omentum

Abstract: The simultaneous association of gastric carcinoma with omental mucosa-associated lymphoid tissue (MALT) lymphoma is a rare event that has not been reported previously. We focused on the hypothetic pathogenetic mechanisms, diagnosis and treatment of this rare condition. A 55-year-old woman with Helicobacter pylori infection underwent distal gastrectomy in our hospital. Three independent early gastric cancers and a mass near the cecum were diagnosed preoperatively. Pathological review of the resected stomach sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[282,283] In our review, H. pylori infection was present in 48.7% of the cases of gastric adenocarcinoma and MALT lymphoma. [39,43,86,90,95,112,130,165,221,242] A remarkable finding summarized in the present review was the cases with the presence of solid tumor metastasis in lymph nodes with lymphomas. A total of 29 cases were seen [12][13][14]40,61,[70][71][72]78,84,92,102,114,115,154,159,191,197,207,208,226,233] (Table 3).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…[282,283] In our review, H. pylori infection was present in 48.7% of the cases of gastric adenocarcinoma and MALT lymphoma. [39,43,86,90,95,112,130,165,221,242] A remarkable finding summarized in the present review was the cases with the presence of solid tumor metastasis in lymph nodes with lymphomas. A total of 29 cases were seen [12][13][14]40,61,[70][71][72]78,84,92,102,114,115,154,159,191,197,207,208,226,233] (Table 3).…”
Section: Discussionmentioning
confidence: 53%
“…1). [12–262] The data were extracted from the abstract in 34 articles, [17,37–39,64,75,76,78,81,94,97,103,129,134,151,162,166,170,174,176,192,195,212,221,222,229,232,234,251,252,256,260–262] of which 21 were in English, 5 in Japanese, 3 in Spanish, 2 in French, 2 in Chinese, and 1 in Czech.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature review found some clinical reports of coexisting diagnoses of gastric MALT lymphoma and sporadic DGC, but none reporting gastric MALT lymphoma in CDH1 mutation patients [19-21]. This can be explained by the low prevalence/underdiagnosis of HDGC and the prophylactic/curative gastrectomy early in life which reduces the chance of this kind of lymphoma developing.…”
Section: Discussionmentioning
confidence: 97%
“…Simultaneous occurrence of gastric carcinoma with omental MALT lymphoma is very rare ( 2 ). Both primary gastric carcinoma and MALT lymphoma are thought to be associated with H. pylori infection ( 3 ).…”
Section: Introductionmentioning
confidence: 99%